(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The study shows how much influence social media has on ABM students in their business marketing strategies; it also consists of different opinions expressed from purposive sampling. This research was done by gathering information through a survey questionnaire with participants from Bestlink College of the Philippines in Quezon City. Based on the results of the study, marketing strategies in Students addressed the above-cited extent and helped the Grade 12 ABM Students to recognize and effectively use social media as a tool in terms of Customer Engagement- creating a bond with customers helps the customer feel a connection with the business. Marketing Cost. It helps businesses to track marketing costs easily. Attraction to a Bigger Audience- It helps businesses improve their search engines. Competition helps businesses to find new concepts. Brand Loyalty helps businesses to build relationships. Cost offers customers cost-effective products that help the business gain more customers. Sales help businesses distinguish the number of new customers who bought per period. Management through proper advertising can help a business develop good management skills. Brand Awareness through search engines can help business owners publicize their products. Customer Service- Provides support to both prospective and existing customers. Data Connections- Being aware of the customer’s internet connection can make the business owners. Communication is one of the important keys of businesses. Scammers- Business owners should be aware of the problems faced by the customers and their Businesses. Cyber Security- Business owners must also prioritize the security of the software they are using. Product Shipments- Businesses must improve visibility throughout the shipping process. Social media can help a business person to engage with their customers and get feedback about their business. Business people can use social media in various ways to improve their marketing strategy, such as advertising and promotional giveaways. Researchers may help future researchers by giving them information for potential improvement of social media benefits and impact on businesses, helping them to gain more customers, review feedback, and build customer loyalty.